Worker Preferences for Flexible Working Arrangements in Prospective Jobs - Haley, M. Ryan; Miller, Laurie A. (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">We apply probit analysis to respondent-level data reported in the 2008 National Study of the Changing Workforce to decompose respondents’ stated preference for workplace flexibilities. We base our analysis on a unique question that asks workers how much they would value workplace flexibilities if they were searching for a new job. The data are very detailed, which allows us to include an array of covariates that may account for the observed variation in flexibility preferences. Covariates such as gender, number of children under the age of 18, sleep problems, work-family conflict, and stress are positively correlated with flexibility preference. Other covariates, such as firm size and public employee status are negatively correlated with flexibility preference. We found mixed evidence for respondents’ age, health status, race, and ethnicity.